Comparison Between Flat and Round Peaches, Genomic Evidences of Heterozygosity Events - Tan, Qiuping; Liu, Xiao; Gao, Hongru; Xiao, Wei; Chen, Xiude; Fu, Xiling; Li, Ling; Li, Dongmei; Gao, Dongsheng (Frontiers in Plant Science, 2019)
Bud sports occur in many plant species, including fruit trees. Although they are correlated with genetic variance in somatic cells, the mechanisms responsible for bud sports are mostly unknown. In this study, a peach bud sport whose fruit shape was transformed to round from flat was identified by next generation sequencing (NGS), and we provide evidence that a long loss of heterozygosity (LOH) event may be responsible for this alteration in fruit shape. Moreover, compared to the reference genome, we identified 237,476 high quality single nucleotide polymorphisms (SNPs) in the wild-type and bud sport genomes. Using this SNP set, a long loss of heterozygosity (LOH) event was identified at the distal end of scaffold Pp06 of the bud sport genome. Haplotypes from 155 additional peach accessions were phased, suggesting that the homozygous distal end of scaffold Pp06 of the bud sport was likely derived from only one haplotype of the wild-type flat peach. A genome-wide association study (GWAS) of 127 peach accessions was conducted to associate a SNP found at 26924482 bp of scaffold Pp06 to differences in fruit shape. All accessions with round-shaped fruit were found to have an A/A genotype, while those with A/T or T/T genotypes had flat-shaped fruits. Finally, we also found that 236 peach accessions and 141 Prunus species with round-type fruit were found to have an A/A genotype at this SNP, while 22 flat peach accessions had an A/T genotype. Taken together, our results suggest that genes flanking this A/T polymorphism and haplotyped carrying the T allele may determine flat fruit shape in this population. Furthermore, the LOH event resulting in the loss of the haplotype carrying the T allele may therefore be responsible for fruit shape alteration in wild-type flat peach.